2007
DOI: 10.1001/archinte.167.4.382
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Atherosclerosis and Risk of Atrial Fibrillation

Abstract: Background: Myocardial infarction is an important risk factor for atrial fibrillation, but the role of subclinical atherosclerosis is unknown. This longitudinal study evaluates whether atherosclerosis affects the risk of atrial fibrillation in persons without overt coronary disease. Methods: This investigation was part of the Rotterdam Study, a population-based cohort study among persons 55 years or older. Participants with atrial fibrillation at baseline, with a history of myocardial infarction, or with angin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 37 publications
5
78
1
4
Order By: Relevance
“…Indeed, data indicate the increased inflammatory burden in patients with AF, connecting the presence of atherosclerosis and incident AF 12. These postulates are also corroborated by other studies underlining a strict relationship between another sign of systemic atherosclerosis, the intima‐media thickness, and AF 13, 14. From this perspective, we should probably start considering the onset of AF as the last stage of a multiple‐stage process, spanning throughout the entire lifetime, beginning with the presence of multiple risk factors and progressing throughout the development of systemic atherosclerosis and diagnosis of PAD (Figure 2).…”
Section: Accumulating Evidence For a New Pathophysiological Paradigmsupporting
confidence: 70%
“…Indeed, data indicate the increased inflammatory burden in patients with AF, connecting the presence of atherosclerosis and incident AF 12. These postulates are also corroborated by other studies underlining a strict relationship between another sign of systemic atherosclerosis, the intima‐media thickness, and AF 13, 14. From this perspective, we should probably start considering the onset of AF as the last stage of a multiple‐stage process, spanning throughout the entire lifetime, beginning with the presence of multiple risk factors and progressing throughout the development of systemic atherosclerosis and diagnosis of PAD (Figure 2).…”
Section: Accumulating Evidence For a New Pathophysiological Paradigmsupporting
confidence: 70%
“…17 IMT is correlated with systemic atherosclerosis and predicts the risk of recurrent strokes. [18][19][20] Recently published articles 21,22 suggested that MDCTA can evaluate the thickness of the carotid artery wall, referred to by Saba et al 21 as CAWT, and presented results indicating significant agreement between MDCTA and CD-US in the measurement of CAWT and IMT. 22 The purpose of this work was to investigate whether CAWT studied by using MDCTA is correlated with LA and its severity.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Among patients with ischemic stroke, a low CIMT has been reported to have a high negative predictive value for the detection of complex aortic plaques, which are among the most prevalent CSE identified on TEE. 8 -13 Other evidence suggests that modern transthoracic echocardiography with bubble study is highly sensitive for the detection of intra-atrial communications, another commonly identified potential CSE after stroke.…”
mentioning
confidence: 99%